Pengaruh Komposisi Polivinilpirolidon (PVP K-30) dan Etil Selulosa (EC N-22) terhadap Prosentase Kelembapan Air dan Laju Pelepasan Meloksikam dalam Sediaan Plester - Selly Rio Wardhani; Lidya Ameliana; Budipratiwi Wisudyaningsih (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
The object of this study was to prepare and evaluated a matrix type transdermal patch of meloxicam using blend of polyvinylpyrolidone (PVP K-30) and ethylcellulose (EC N-22) were 1:9 (Formula I); 2:8 (Formula II); and 3:7 (Formula III). Evaluation of patch is organoleptic, percentage moisture content, and the release of the drug. Results were analyzed by statistic programmed of SPSS using one way analysis of variance with degree of believed 95% ( = 0.05). The results of organoleptic evaluation of patch dosage, transdermal patches were found yellow, odorless, and dry. Results test percentage moisture content (Formula I) 1.501 ± 0.022 %; (Formula II) 2.206 ± 0.010 %; dan (Formula III) 3.725 ± 0.033 %. Results test flux (Formula I) 455.078 ± 0.835 μg/cm2/menit1/2; (Formula II) 539.08 ± 0.835 μg/cm2/menit1/2; dan (Formula III) 677.851 ± 0.799 μg/cm2/menit1/2. It can be concluded that the combination of polyvinylpyrolidone (PVP K-30) and ethylcellulose (EC N-22) at ratio 3:7 was the best choice for manufacturing transdermal patch based on release profile.